Phase transitions in clusters - Berry, R.S.; Smirnov, B.M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2009)
General concepts of cluster phase transitions are reviewed as well as the cluster behavior near the melting point. Configuration excitation determines the nature of the cluster phase transitions, but a significant contribution to the entropy jump is given by thermal motion of atoms that allows one to characterize the phase transition through thermal atom motion in the Lindemann and other criteria. The phase coexistence near the melting point is the peculiarity of not large clusters. The void concept of phase transitions with a void as an elementary configuration excitation allows one to describe the phase transition for clusters and macroscopic atomic systems. Phase transitions in metal clusters resemble those in clusters with pairwise atomic interactions, but their numerical parameters are other because of a large number of isomers and an additional electron degree of freedom. Cluster models are convenient for the analysis of macroscopic atomic systems. They allow us to understand the nature of glassy transitions and the reason of absence of a stable infinite crystal lattice for gases at zero temperature and high pressure.